2022
DOI: 10.3390/ijms232415825
|View full text |Cite
|
Sign up to set email alerts
|

MTARC1 and HSD17B13 Variants Have Protective Effects on Non-Alcoholic Fatty Liver Disease in Patients Undergoing Bariatric Surgery

Abstract: The severity of hepatic steatosis is modulated by genetic variants, such as patatin-like phospholipase domain containing 3 (PNPLA3) rs738409, transmembrane 6 superfamily member 2 (TM6SF2) rs58542926, and membrane-bound O-acyltransferase domain containing 7 (MBOAT7) rs641738. Recently, mitochondrial amidoxime reducing component 1 (MTARC1) rs2642438 and hydroxysteroid 17-beta dehydrogenase 13 (HSD17B13) rs72613567 polymorphisms were shown to have protective effects on liver diseases. Here, we evaluate these vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In this study we used exome-wide association analysis in over 500,000 individuals to identify several novel rare pLOFs variants in MARC1 with phenotypes similar to previously reported p.Ala165Thr (A165T) and p.Met187Lys (M187K) variants [11][12][13][14][15][16][17][18][19]. We showed p. A165T substitution in MARC1 causes protein instability, leading to the lower MARC1 protein levels in the livers of human carriers of MARC1 p.A165T variant, confirming this variant is a loss of function.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this study we used exome-wide association analysis in over 500,000 individuals to identify several novel rare pLOFs variants in MARC1 with phenotypes similar to previously reported p.Ala165Thr (A165T) and p.Met187Lys (M187K) variants [11][12][13][14][15][16][17][18][19]. We showed p. A165T substitution in MARC1 causes protein instability, leading to the lower MARC1 protein levels in the livers of human carriers of MARC1 p.A165T variant, confirming this variant is a loss of function.…”
Section: Introductionmentioning
confidence: 62%
“…These studies revealed several missense variants that are associated with lipid accumulation and NAFLD progression [3][4][5][6][7][8][9][10]. Recent genome-wide association studies discovered that common MARC1 missense variants (p. A165T, rs2642438 G>A and p.M187K, rs17850677 T>A) and several rare MARC1 putative loss of function (pLOF) variants (p.R200Ter, p.R305Ter) in humans are associated with decreased liver fat, lower blood ALT, lower alkaline phosphatase, reduced LDL and total cholesterol, as well as protection from all-cause of liver cirrhosis [11][12][13][14][15][16][17][18][19]. MARC1 (mitochondrial amidoxime-reducing component 1, known also as MOSC1 and MTARC1) is a molybdenum containing enzyme anchored on the outer mitochondria membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Several human genes with potential causal relationships to MASH phenotypes have been discovered through population genetics approaches, including the mitochondrial amidoxime–reducing component 1 gene ( MTARC1 , encoding outer mitochondrial membrane protein mARC1). 8 9 10 11 12 13 Missense and nonsense variants in MTARC1 were identified in a genome-wide association study (GWAS), which implicated these variants in protecting their carriers from MASH phenotypes, including reduced risk for MASH, hepatic steatosis, liver enzyme elevations, cirrhosis, and all-cause liver-related mortality. 9 12 …”
Section: Introductionmentioning
confidence: 99%
“… 8 9 10 11 12 13 Missense and nonsense variants in MTARC1 were identified in a genome-wide association study (GWAS), which implicated these variants in protecting their carriers from MASH phenotypes, including reduced risk for MASH, hepatic steatosis, liver enzyme elevations, cirrhosis, and all-cause liver-related mortality. 9 12 …”
Section: Introductionmentioning
confidence: 99%
“…Hepatic steatosis is common among patients scheduled for bariatric surgery, and steatohepatitis and liver fibrosis have been reported as potential complications of traditional jejunoileal bypass surgery [ 14 ]. Kalinowski et al also reported that mitochondrial amidoxime reducing component 1 (MTARC1) rs2642438 and hydroxysteroid 17-beta dehydrogenase 13 (HSD17B13) rs72613567 polymorphisms had protective effects on nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH) [ 15 ], although functions of these gene-coding proteins should be further explored.…”
mentioning
confidence: 99%